How to pray salat - Khan, Saniyasnain (Goodword Books New Delhi, 2008)
"How to Pray Salat" is a practical guide that provides clear and step-by-step instructions on performing the Islamic prayer (Salat), helping both beginners and experienced Muslims understand its significance, rituals, and proper techniques.